EVALUATION OF THE ANTIBACTERIAL ACTIVITY OF METHANOLIC EXTRACT FROM CORELLOCORPUS EPIGAEUS TUBER - SWARNALATHA.Y (International Journal of Pharma and Bio Sciences, 2015)
Tuber powder of the Corellocorpus epigaeus was investigated for antibacterial activity against the gram positive and gram negative microorganisms. Methanolic extract of the tuber was evaluated against five common isolates which includes E.Coli, Proteus vulgaris, Serratia, Pseudomonas and Micrococcus. Qualitative analysis of the metholic extract revealed the presence of the flavonoids, alkaloids, phenolic compounds, tannins, proteins, aminoacids, fats and carbohydrates. Methanolic extract of Corallocarpus epigaeus tuber showed better antimicrobial activity on gram negative microorganisms than gram positive organisms. This property was also identified in growth curve studies. Both the studies carried out proved the antibacterial activity of Corallocarpus epigaeus